Pengaruh Inovasi, Brand Ambassador, dan Promosi terhadap Keputusan Pembelian Scarlett Whitening pada Media Sosial Tiktok Batam - Fenilia Fenilia; Inda Sukati (Pascasarjana STIE Amkop Makassar, 2023)
This researches are conduct on the Tiktok Batam social media, especially for consumers who use products from Scarlett Whitening. The aims of these researches are finding out and innovation, brand ambassadors, and promotions on purchasing decisions. The populations and sample are the peoples in Batam who use Tiktok who use Scarlett Whitening beauty products, totaling 100 people. Data collection conducted by distributing questionnaires. The data analys deployed multiple linear regressions. The finding showed that innovation, brand ambassadors, and promotions partially and simultaneously influence the purchasing decision of scarlett whitening on the Tiktok Batam social media. The Adjusted R Square value of 0.550, that meaning that innovation, brand ambassadors, and promotion of purchasing decision representatives is 55% and the remaining 45% is influenced by other variables outside of this study such as price, product quality, brand, and so on. Keywords: Brand Ambassador, Innovation, Promotion, Purchase Decision